Reconciling Contradictory Findings: In Silico Evaluation of Annonacin’s Antimalarial Efficacy and Safety - Anindya Zerlina Tsaqif; Khodijah Khodijah; Fahrizal Ryuzen Prayogi; Moh Mirza Nuryady; Kiky Martha Ariesaka (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2025)
Introduction. With the increasing resistance to existing antimalarial therapies, the discovery of new drugs has become urgent. Annona muricata contains phenolic compounds with antioxidant potential and bioactive properties, including annonaceous acetogenins, which exhibit cytotoxicity, raising safety concerns. Conversely, other studies have shown significant antimalarial activity from A. muricata extracts without observed toxicity, suggesting its potential as a lead compound for malaria treatment. This inconsistency calls for further investigation, particularly through in silico analyses, to clarify the interactions between these compounds and key malaria targets. Aim. This study employs in silico methods to explore Annonacin’s binding affinity to malaria proteins, PfDHODH and PfLDH, and evaluates its toxicity and bioavailability. Methods. Molecular docking was conducted using Molegro Virtual Docker (MVD) version 6.0 to assess Annonacin’s binding interactions with PfDHODH and PfLDH. Toxicity was analyzed using ProTox-II, focusing on cytotoxicity and LD50 value. Pharmacokinetic properties, including gastrointestinal absorption and adherence to Lipinski’s rule of five, were evaluated using SwissADME. Results. Docking results revealed that Annonacin forms stable complexes with both proteins, suggesting strong inhibitory potential. However, toxicity analysis highlighted significant cytotoxic effects, with an LD50 of 400 mg/kg placing Annonacin in Toxicity Class IV, indicating ingestion risks. Pharmacokinetic analysis revealed challenges such as low gastrointestinal absorption and a violation of Lipinski’s rule due to high molecular weight. Conclusion. These findings suggest Annonacin has antimalarial potential, but its development is hindered by safety concerns and pharmacokinetic limitations. Further optimization is needed to balance efficacy with safety, providing a foundation for future research and development.